Examining the Nexus Between Income Diversification, Profitability and Risk of Brazilian Banks: A Dynamic Panel Data Analysis - Kanwaljeet Singh, Dr Manjit Singh, Dr Rajdeep Singh (European Economic Letters (EEL), 2025)
The study examines how bank profitability and risk are impacted by income and asset diversification in Brazilian developing banking industry. The researchers employ a dynamic panel model with System GMM estimate on a panel data of 125 banks between 2011 and 2022 to account for the persistence of bank performance and risk. The findings indicate that income and asset diversification both considerably improve risk-adjusted profitability as indicated by risk adjusted return on assets (RROA) and risk adjusted return on equity (RROE) and but increasing bank risk as indicated by the standard deviation of returns (σ(ROA) and σ(ROE)). These findings show how diversification is strategically valuable for enhancing resilience and financial success in an unpredictable economic climate. The report advocates for risk-sensitive innovation and diverse development methods and provides useful insights for regulators, policymakers, and bank management.